Targeting Innate Immunity in Breast Cancer Therapy: A Narrative Review - Ye, Yanqi; Xu, Chun; Chen, Fengqian; Liu, Qi; Cheng, Ning (Frontiers in Immunology, 2021)
Although breast cancer has been previously considered "cold" tumors, numerous studies are currently conducted to explore the great potentials of immunotherapies in improving breast cancer patient outcomes. In addition to the focus on stimulating adaptive immunity for anti-tumor responses, growing evidence showed the importance of triggering host innate immunity to eradicate established tumors and/or control tumor metastasis of breast cancer. In this review, we first briefly introduce the breast tumor immune microenvironment. We also discuss innate immune targets and pathways, and mechanisms of their synergy with the adaptive anti-tumor response and other treatment strategies. Lastly, we review clinical trials targeting innate immune pathways for breast cancer therapies.